1982
DOI: 10.2172/5942981
|View full text |Cite
|
Sign up to set email alerts
|

Fuels for research and test reactors, status review: July 1982

Abstract: U0 2 U0 2 U0 2 9.Microstructures of U 3 SiAl (U + 3.5 wt% Si + 1.5 wt% Al). Curves A-D show heat-flow data for fuels with x -1.58, 1.65, 1.7, and 1.8, respectively. Lines UL, LL, and MP indicate the upper limit, lower limit, and most probable value, respectively, for the thermal conductivity of fuel with x -1.6. Line A shows pulse-heating data for fuel with x -1.6, which do not agree with curve MP. ABSTRACTA thorough review is provided on nuclear fuels for steady-state thermal research and test reactors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The development of spot features at high doses (>80 dpa) indicates that the microstructure evolution continues beyond 100 dpa at this irradiation temperature. Considering the melting temperature of $1350°C for UAl 3 type phase [14], the development of large loops at a relatively low irradiation temperature (T irr /T melt = 0.29) suggests a high mobility of point defects in this phase. Superdislocations can form in the ordered structure, such as intermetallic compounds of AB 3 or A(B,C) 3 -type fcc structures where atom-A occupies the corner sites of the cubic unit cell [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The development of spot features at high doses (>80 dpa) indicates that the microstructure evolution continues beyond 100 dpa at this irradiation temperature. Considering the melting temperature of $1350°C for UAl 3 type phase [14], the development of large loops at a relatively low irradiation temperature (T irr /T melt = 0.29) suggests a high mobility of point defects in this phase. Superdislocations can form in the ordered structure, such as intermetallic compounds of AB 3 or A(B,C) 3 -type fcc structures where atom-A occupies the corner sites of the cubic unit cell [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There were a few studies that investigated the corrosion behavior of Al-U 3 O 8 dispersion fuels with defected cladding. 127,128,129 Peacock recently reviewed the properties of Al-U 3 O 8 fuel. 130 Peacock considered the corrosion behavior generally the same as that of the aluminum matrix, since the reaction rate of U 3 O 8 with water is very small in comparison.…”
Section: Dmentioning
confidence: 99%
“…Since there is no apparent reason for the UA1 X -A1 thermal conductivity to be significantly lower than that for U 3 O 8 -A1 fuel, one suspects that the data may be in error. In fact, Stahl (1982), in an earlier compilation of thermal conductivity data, concluded that these particular specimens were not well-characterized and that the measurement system was not well-calibrated. One might expect UAl^ dispersions to behave like U 3 Si 2 dispersions since they have many other similarities.…”
Section: Powder Metallurgy Fuelsmentioning
confidence: 99%
“…It has generally been assumed (Stahl, 1982) that the thermal expansion of the dispersion is essentially controlled by the expansion of the Al matrix, since the expansion coefficient for Al is 1.5 to 3 times that of the uranium aluminides (~ 16 x 10" 6 ), the uranium oxides (~ 9 x 10 " 6 ), and the uranium silicides (~ 15 x 10 ~6). However, measurements performed by Nazare et al (1975) showed that this assumption is not completely valid.…”
Section: Coefficient Of Thermal Expansionmentioning
confidence: 99%
See 1 more Smart Citation